Botulinum toxin on a mission to erase keloids: does the dream come true? - Fratczak, Aleksandra; Spyra, Aleksandra; Pawlus, Zuzanna; Polak, Karina; Bergler-Czop, Beata (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2025)
Keloids are fibrous scars that result from a variety of factors causing skin damage. Botulinum toxin, especially the most widely utilized serotype A, is used for many purposes in both medical and aesthetic practices. Numerous studies indicate the beneficial effects of using botulinum toxin in the treatment of scars, including keloids. The aim of this study was to explore the current evidence behind the use of botulinum toxin in the prevention and treatment of keloids. PubMed was searched using medical subject headings to identify studies on this topic. All analysed studies confirmed the effectiveness of intralesional injections of botulinum toxin in keloid therapy. Significant improvement in the appearance and size of lesions, histopathological findings, patient satisfaction, and reduction in symptoms are observed. Further research is required to ascertain the significance of this therapeutic approach in keloid treatment protocols.